1996
DOI: 10.1177/088626096011002009
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning as Predictors of Distress in Revictimized Sexual Abuse Survivors

Abstract: The present study examines the distress symptomatology and family functioning in female undergraduate students who had been sexually victimized in childhood and revictimized in adulthood. This group was contrasted with a child sexual abuse group, peer sexual abuse group, and a no sexual trauma group. Findings indicated that the revictimized group reported the most severe forms of sexual assault relative to other victimized groups. The victimized groups were all significantly more distressed than the nonabused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 15 publications
3
43
1
Order By: Relevance
“…This latter finding suggests that there may be a cumulative effect of multiple sexual traumas and replicates findings with heterosexual women that revictimization is associated with greater psychological difficulties (e.g., Cloitre et al, 1997;Follette et al, 1996;Gidycz et al, 1993;Koverola et al, 1996;Murphy et al, 1988). Although many individuals, particularly those in the sexual revictimization group, reported at least moderate levels of psychological symptomatology, a comparison of our group means to the adult psychiatric standardized group means for each measure provided in Table 2 reveals that with the exception of BSI GSI scores, our sample did not generally report symptomatology on a level comparable to that reported by either psychiatric inpatients or outpatients.…”
Section: Discussionsupporting
confidence: 77%
“…This latter finding suggests that there may be a cumulative effect of multiple sexual traumas and replicates findings with heterosexual women that revictimization is associated with greater psychological difficulties (e.g., Cloitre et al, 1997;Follette et al, 1996;Gidycz et al, 1993;Koverola et al, 1996;Murphy et al, 1988). Although many individuals, particularly those in the sexual revictimization group, reported at least moderate levels of psychological symptomatology, a comparison of our group means to the adult psychiatric standardized group means for each measure provided in Table 2 reveals that with the exception of BSI GSI scores, our sample did not generally report symptomatology on a level comparable to that reported by either psychiatric inpatients or outpatients.…”
Section: Discussionsupporting
confidence: 77%
“…Fleming and colleagues (1999) found that CSA involving intercourse tripled the risk of rape in adulthood. CSA with penetration was more commonly reported by revictimized women and those with more severe PTSD symptoms (Classen et al, 2005;Koverola et al, 1996). Ullman and associates (2006) found that individuals with greater CSA severity were one and a half times more likely to blame themselves at the time the abuse occurred and more than twice as likely to blame themselves currently for the abuse.…”
Section: Child Sexual Abuse Characteristics Theorized To Influence Trmentioning
confidence: 99%
“…The racial/ethnic background of the victim is now understood to be a major influence on the meaning and interpretation of SA for the individual as well as the response from others if/when abuse is revealed (Behl, Crouch, May, & Valente, 2001;Bohn, 2003;Urquiza & Goodlin-Jones, 1994;Wyatt, Guthrie, & Notgrass, 1992). A detailed sexual history, including severity, duration, frequency, use of force, number of perpetrators, and relationship to perpetrators are all variables critical to health outcomes and risks for sexual revictimization (Arata, 2000;Bifulco, Brown, & Adler, 1991;Collins, 1998;Kessler & Bieschke, 1999;Koverola, Proulx, Battle, & Hanna, 1996;West, Williams, & Siegel, 2000;Wyatt, Loeb, Solis, Carmona, & Romero, 1999). Recency of abuse in relation to the assessment appears important; the more recent the abuse, the greater the likelihood that it will predict revictimization (Himelein, 1995).…”
Section: Personal and Interpersonal Level Factorsmentioning
confidence: 99%
“…A detailed history of other forms of trauma including child physical abuse and family adversity have also been linked to negative sequelae (Molnar, Buka, & Kessler, 2001) and sexual revictimization (Arata & Lindman, 2002;Desai, Arias, Thompson, & Basile, 2002;Heidt, Marx, & Gold, 2005;Jankowski, Leitenberg, Henning, & Coffey, 2002). Family structure and dynamics and interpersonal relationships should be assessed including the composition of the family unit and of primary social groups, the use of alcohol and drugs by members in these groups, and the methods for resolution of conflict are also relevant issues (Hamilton & Browne, 1999;Kellogg & Hoffman, 1997;Koverola et al, 1996;Long & Jackson, 1991;Nash, Hulsey, Sexton, Harralson, & Lambert, 1993;Nelson et al, 2002;Swanston et al, 2002). Psychiatric disorders (e.g., depression and anxiety or substance abuse) as well as psychological factors (e.g., shame, self-blame, and resiliency) are critical variables to explore (Neumann, Houskamp, Pollock, & Briere, 1996).…”
Section: Personal and Interpersonal Level Factorsmentioning
confidence: 99%